Risk management techniques in emerging markets - Hoguet, George R. (Henry Stewart Talks, 2014)
Emerging market risks, Portfolio construction, Convergent/divergent strategies, Lessons of the great recession and global financial crisis, Characteristics of emerging market capital markets, Emerging market equity and debt capitalization weights, Emerging market correlations with major asset classes, Emerging market return distributions, Valuation models, Advanced beta strategies, Managed volatility strategies, Tactical asset allocation, Active portfolio management, Risk management